Factions and political competition - Persico, Nicola 1967-; Rodríguez-Pueblita, José Carlos; Silverman, Dan (National Bureau of Economic Research, 2007)
This paper presents a new model of political competition where candidates belong to factions. Before elections, factions compete to direct local public goods to their local constituencies. Voters view the public goods as a credible signal that their local candidate is in the right (i.e., powerful) faction. The model of factional competition delivers a rich set of implications relating the internal organization of the party to the allocation of resources. Several key theoretical predictions of the model find a counterpart in our empirical analysis of newly coded data on the provision of water services in Mexico.